Public Investment in Agricultural Growth in the West African Monetary Union (UEMOA) - ADEGNIKA, MOUTAÏROU; MOUNIROU, ICHAOU (My University, 2019)
This article analyze the impacts of public investments on agricultural growth in the West African Economic Monetary Union (WAEMU). Fixed effect panel models have been developed. The sample used covers 8 African countries over the period 1961 to 2016. The results of the estimations indicate that agricultural public investments have positive and significant elasticity’s on agricultural growth and that this impact depends on the combination with the other factors of agricultural growth, as pointed out by some authors. On the other hand, the panel III model shows that other factors such as the price of cotton to producers, the volumes of rainfall, the number of tractors and the active agricultural population also condition good agricultural growth. Nevertheless, the quantities of urea, the production and area of cotton do not have a significant impact on agricultural growth. For effective agricultural growth in this area, the adoption of chemical and mechanical innovations and substantial agricultural public investment becomes imperative and a necessary and sufficient condition to boost a true green revolution. Moreover,our results suggest that the main channel for sustainable agricultural growth in the union is the combination of all factors of production.
Keywords: agricultural public investment; agricultural growth; panel data model